(untitled) (American Journal of Islam and Society, 1997)
This book analyzes Indonesia’s political and economic commitment to ASEAN. ASEAN compries six Southeast Asian countries: Brunei, Indonesia, Malaysia, the Philippines, Singapore, and Thailand. To clarify that commitment, Anwar makes a deliberate attempt to investigate ASEAN’s underlying assumptions. Specifically, the organization is intended to promote harmony and peace in the region, given that ASEAN countries are relatively more politically stable and economically developed compared to the nearby Indochinese states. In adrution, ASEAN has been perceived as attempting to manage regional order agrunst nonregional powers such as Chma while strengthening Western ties. The author examines these assumptions on the premise that ASEAN is mainly a distinctive vehicle of Indonesian foreign policy. To do so, he follows Weinstein’s approach, which I based on the uses of foreign policy, that is, his analysis does not adopt a common theory. Thus, he unintentionally goes back and forth to verify what seems to be the main theme of the book: how Indonesia sought regional leadership through ASEAN to achieve its main goals of foreign policy ...